Subsidence rings and fracture pattern around dolines in carbonate platforms – Implications for evolution and petrophysical properties of collapse structures. (March 2020) - Menezes, Daniel F.; Bezerra, Francisco H.; Balsamo, Fabrizio; Arcari, Andrea; Maia, Rubson P.; Cazarin, Caroline L.
Abstract: This work focuses on the study of collapse dolines, which are the most expressive collapse structures in carbonate rocks, and their relations with preexisting and syn-collapse fractures. The study area has two fracture sets that were formed before folding, early N-S/E-W- and late NE-SW/NW-SE-striking sets, which concentrate most of the dissolution in the region and allow the formation of the dolines. We define subsidence rings as the circular and ellipsoidal concentric zones around collapse structures, which are subjected to subsidence due to major collapses and represent locations where new fractures are formed. In these subsidence rings, the downfaulted topography plunges towards the doline center and reaches more than 10 m in relation to unaffected areas away from dolines. The topographic data indicate that the mean radius of the combined rings is twice the radius of the collapse, which corresponds to the closed depression due to failure and downfall of blocks. The subsidence process enlarges, links preexisting fractures, and forms a new set of semicircular concentric opening mode fractures, here named collapse fractures. Increases in the apertures and densities of these fractures occur towards the dolines, which increases fracture porosity around collapse structures. Fractures are reactivated as normal faults close to the main collapse at the doline edge. This increase in fracture intensity could represent an indicator of permo-porous quality improvement in these areas. Further, this fracturing increases structural instability, raising the risk of accidents in areas built on soluble carbonate rocks, since the affected area may be much larger than previously predicted. Subsidence rings around collapse dolines could merge with other rings from neighboring collapse structures and potentially increase porosity and permeability, as well as linking areas in carbonate reservoirs. Highlights: Subsidence rings are highly fractured zones around dolines prone to collapse. Gravity-induced, semicircular open-mode collapse fractures occur in the rings. Collapse fractures reactivate and reopen preexisting background fracture sets. The total subsidence ring width is twice the radius of the related doline. Subsidence rings coalesce and form highly fractured areas around collapse structures.